CD86 Is a Selective CD28 Ligand Supporting FoxP3+ Regulatory T Cell Homeostasis in the Presence of High Levels of CTLA-4 - Halliday, Neil; Williams, Cayman; Kennedy, Alan; Waters, Erin; Pesenacker, Anne M.; Soskic, Blagoje; Hinze, Claudia; Hou, Tie Zheng; Rowshanravan, Behzad; Janman, Daniel; Walker, Lucy S. K.; Sansom, David M. (Frontiers in Immunology, 2020)
CD80 and CD86 are expressed on antigen presenting cells and are required to engage their shared receptor, CD28, for the costimulation of CD4 T cells. It is unclear why two stimulatory ligands with overlapping roles have evolved. CD80 and CD86 also bind the regulatory molecule CTLA-4. We explored the role of CD80 and CD86 in the homeostasis and proliferation of CD4+FoxP3+ regulatory T cells (Treg), which constitutively express high levels of CTLA-4 yet are critically dependent upon CD28 signals. We observed that CD86 was the dominant ligand for Treg proliferation, survival and maintenance of a regulatory phenotype, with higher expression of CTLA-4, ICOS and OX40. We also explored whether CD80-CD28 interactions were specifically compromised by CTLA-4 and found that antibody blockade, clinical deficiency of CTLA-4 and CRISPR-Cas9 deletion of CTLA-4 all improved Treg survival following CD80 stimulation. Taken together, our data suggest that CD86 is the dominant costimulatory ligand for Treg homeostasis, despite its lower affinity for CD28, because CD80-CD28 interactions are selectively impaired by the high levels of CTLA-4. These data suggest a cell intrinsic role for CTLA-4 in regulating CD28 costimulation by direct competition for CD80, and indicate that that CD80 and CD86 have discrete roles in CD28 costimulation of CD4 T cells in the presence of high levels of CTLA-4.